Yona of the dawn. 20 - Kusanagi, Mizuho, 1979-; MacFarlane, Ysabet Reinhardt (Shojo beat manga., 2019)
Princess Yona lives an ideal life as the only princess of her kingdom. Doted on by her father, the king, and protected by her faithful guard Hak, she cherishes the time spent with the man she loves, Su-won. But everything changes on her 16th birthday when tragedy strikes her family! Yona and Riri wind up in the nation of Sei after being betrayed by a trusted acquaintance! Forced to work as slaves, the two stubbornly refuse to be controlled, but their situation is dire. In order to save Yona and Riri, Hak and the Four Dragons split into two groups and sneak into enemy territory!